Drp1 Regulated Mitochondrial Hypofission Promotes the Invasion and Proliferation of Growth Hormone-Secreting Pituitary Adenomas via Activating STAT3 - Zhang, Yin; Zhang, Lei; Fan, Kexia; Gou, Yajun; Zang, Zhenle; Ding, Xiao; Yang, Hui; Li, Song (Frontiers in Oncology, 2022)
The invasiveness and high proliferation of growth hormone-secreting pituitary adenomas (GHPAs) are closely related to poor prognosis in patients. We previously reported that abnormal glycolysis participates in this process; however, the role of mitochondria in the invasion and proliferation of GHPAs remains unknown. In the current study, stereological methods were first used to quantitatively calculate the number and morphology of mitochondria. The results revealed that the numbers, volumes and membrane areas of mitochondria were decreased in invasive GHPAs (IGHPAs) samples compared to noninvasive GHPAs (NIGHPAs) samples. Furthermore, significantly downregulated mRNA and protein levels of dynamin-related protein 1 (Drp1) were detected in IGHPAs, but no notable changes in mitofusin 1 or 2 were detected, suggesting that the abnormal mitochondrial dynamics in IGHPAs are characterized by hypofission. Mitochondrial hypofission caused by Mdivi-1, a specific Drp1 inhibitor, enhanced the invasion and proliferation of GH3 cell lines and primary cells from patients with GHPAs in vitro, while overexpression of Drp1 reversed these processes. Mechanistically, mitochondrial hypofission might activate signal transducer and activator of transcription 3 (STAT3). Specifically, elevated nuclear pSTAT3Y705 may promote GH3 cell invasion by upregulating the activity of matrix metalloproteinase 2/9, and elevated mitochondrial pSTAT3S727 may promote GH3 cell proliferation by inhibiting the mitochondria-dependent apoptotic pathway. Taken together, our findings suggest that mitochondrial hypofission induced by Drp1 might strengthen the invasion and proliferation of GHPA tumor cells by activating STAT3, providing us with a new perspective on how mitochondria regulate the development of IGHPAs.